On a Metaprocess for Microservice Migration - Medeiros, Henrique; Batista, Thais; Cavalcante, Everton (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2023: Anais do XXXVII Simpósio Brasileiro de Engenharia de Software, 2023)
Microservice-based architectures have become popular to manage the complexity of many cloud service-oriented systems and comply with availability, maintainability, and scalability requirements. Modernizing legacy systems to adopt microservices is time-consuming and has often been ad-hoc. One of the main issues is the lack of an understanding of which activities and artifacts should be considered when migrating applications to microservices, besides how to realize a well-defined process to achieve the expected benefits. This paper introduces the Metaprocess for Microservice Migration Kernel (M3K) to support migrating monolithic applications to microservice architectures. The core idea is defining a general-purpose metaprocess that development teams and organizations could use as a basis for defining their specific microservice migration processes. M3K relies on OMG Essence Standard as a well-founded common ground for establishing software development practices, activities, and work products and tracking the migration to microservices.